PENGARUH TINGGI TUMPUKAN PADA PENGOMPOSAN TANDAN KOSONG KELAPA SAWIT MENGGUNAKAN PUPUK ORGANIK AKTIF DARI LIMBAH CAIR PABRIK KELAPA SAWIT DI DALAM KOMPOSTER MENARA DRUM - Chamsa Triyadi; Yosi Rahman; Bambang Trisakti (Jurnal Teknik Kimia USU, 2015)
This research aims to determine the composting technique for Empty Fruit Bunch (EFB) and to collect the degration data during composting of EFB in order to get a high quality compost. The composting process was started with cutting the EFB into four parts before it was put into composter and then followed by the addition of Activated Liquid Organic Fertilizer (ALOF) until the optimum moisture content (MC) of 55-65 % was reached. The parameters of temperature, MC, pH, C/N ratio, Electrical Conductivity (EC), Water Holding Capacity (WHC), Bacterial Count (BC) and the quality of compost were analyzed through the process. The results of this research showed that the compost were well done in about 10 days and the best degradation during the 40 days of composting was obtained in which value of MC, pH, C, N, C/N ratio, EC, WHC and BC were 79,14%; 8,1; 25,16%;1,20%; 20,97; 4,725 dS/m; 60% and 107 CFU/ml, respectively.